(untitled) (Research, Society and Development, 2021)
Contemporary life has demanded new methodologies to deal with education and health care. This paper aims to describe the necessary care for newborn babies after discharge from intensive care unit (ICU) and to discuss with health professionals who work in a Neonatal ICU the guidelines provided to parents and family members, as well as to talk to the latter about the theme. An action research was carried out in a hospital in a city in the countryside of Rio Grande do Sul State, Brazil, in which 14 health professionals and 8 parents and family members have participated. Two categories emerged from the responses to the questionnaire distributed to the health professionals: “General care for the health of the newborn after discharge from the ICU” and “Care for the feeding of the breastfeeding mother. From the first category, four subcategories emerged: “Care for the environment in the home where the newborn will live”; “Care for the baby’s food”; “Care for baby’s clothes” and “Care for baby’s hygiene”. From the responses of parents and family members, two categories emerged: “Preparation for discharge from the ICU” and “Booklet evaluation and main doubts of parents”. The conclusion of this research is that parents and family members need to receive support from the health team, both in hospital care, as in outpatient or home care. The guidelines provided helped considerably in the care of the child at home, since they are easy to understand, enlightening and in accordance with the reality they experienced with the child in the ICU.